Invasive willows drive instream community structure. (24th May 2016) - McInerney, Paul J.; Rees, Gavin N.; Gawne, Ben; Suter, Phil; Watson, Garth; Stoffels, Rick J.
Summary: Exotic invasive species are known to influence taxonomic communities and ecological processes. Few studies have examined the impact on taxonomic communities across trophic levels because it is time consuming and requires a wide range of identification skills. Here, we examined the impacts of invasive willow trees ( Salix spp.) on microbial and macroinvertebrate composition using a combination of high resolution ecogenomic and classical approaches. Aquatic communities were compared and contrasted between stream reaches with and without willow infestation in three temperate Australian streams. Willows significantly altered in‐stream fungal, algal and macroinvertebrate communities. Macroinvertebrate diversity was similar between riparian types. Willow‐infested sites were characterised by lower macroinvertebrate abundance and Australian biotic index scores, indicating the presence of taxa generally more tolerant to pollution. At invaded sites, grazers were replaced by generalist collector–gatherer taxa and the proportions of macroinvertebrate functional‐feeding groups (FFG) were altered such that the primary trophic pathway was changed from an autotrophic algal‐based pathway to a heterotrophic, detrital‐based pathway. Riparian invasion by willows may change the primary source of energy from autotrophy to heterotrophy in small streams, with knock‐on effects on community structure across trophic levels.